Integrated reporting: one report for a sustainable strategy / Roshima Said, Leily Adja Radjeman and Wan Nailah Abdullah - Said, Roshima; Radjeman, Leily Adja; Abdullah, Wan Nailah (Faculty of Accountancy, UiTM Kedah, 2018)
Today, news is easily spread through social media networks and the internet. Consequently, stakeholders such as investors and governments as well as society are increasingly demanding for organizations to provide them with transparent reporting about their activities and be accountable to the stakeholders (Abeysekera, 2013). Although organisations have already begun to be accountable and started to provide reports to the stakeholders, such initiatives seem to not truly reflect the organizations‟ long-term objectives and often provide separate reports like annual reports and sustainability reports which are seen as unconnected activities which the organizations undertake (Abeysekera, 2013). Thus, organizations should provide one report that integrates all the activities which they undertake. “One Report” refers to companies which provide reports that are beyond separate reports for both their financial and non-financial information such as sustainability or corporate social responsibility. Additionally, “One Report” illustrates how integrated reporting can increase the value of the companies and stakeholders as well as contribute to a sustainable society (Eccles & Krzus, 2010).